Contratos administrativos e arbitragem: uma análise da efetivação do princípio da eficiência - Silva, Rafeal Natan do Nascimento (Universidade Federal Rural do Semi-Árido, 2017)
The present research has the objective to analyze the use of arbitration as a dispute resolution in administrative contracts signed between the public and private sector, according the Law 13,129 / 2015, and to demonstrate that this way of conflict resolution could be important for the effective of Principle of administrative efficiency. The methodology used was the deductive, interpretative and analytical approach, based on bibliographical and data research. The large number of lawsuits brought to Brazilian judiciary has become an obstacle to effective jurisdictional service in litigation. Thus, this project brings numbers about the Brazilian Judiciary and their difficulties. In addition, a profile was drawn of how arbitration is used and what are the advantages of this dispute resolution method in all ways. A described was also made on the history of contracts and their importance in Western law, as well the peculiarities of administrative contracts, especially in relation to the exorbitant clauses and the economic and financial balance of the relationship between State and private sector, ensuring the Constitutional guarantees to the contractors and the hired one. Finally, the constitutional principle of administrative efficiency was discussed, showing that arbitration in administrative contracts is a solution for the State’s goal of efficiency.
Monografia
Keywords: Arbitragem; Poder público; Contratos administrativos; Princípio da eficiência; Arbitration; Public power; Administrative contracts; Efficiency principle; CIENCIAS SOCIAIS APLICADAS::DIREITO